DIETARY ENERGY UTILIZATION IN RAMS BEING FED DURING THE DAY AND/OR AT NIGHT - Aprilliza, M.N.; Purnomoadi, A.; Rianto, E. (Journal of the Indonesian Tropical Animal Agriculture, 2014)
A study was carried out to assess dietary energy utilization in male fat-tailed sheep being fed duringthe day and/or at night. This study were used 12 rams of 12-18 months old with average of initial bodyweight of 27.05±2.9 kg (CV = 10.74%). The experimental design used in this study was a completelyrandomized design (CRD) with 3 treatments and 4 replications. The treatments were feeding during theday (06.00-18.00; DF), feeding at night (18.00-06.00; NF), and feeding all day and night (06.00-06.00;DNF). The diet was offered ad libitum. The results showed that feeding during the day and/or at nightdid not significantly affect (P>0.05) all parameters observed. The average of dry matter intake (DMI),average daily gain (ADG), gross energy intake (GEI), energy digestibility (DE) and energymetabolizability (ME) were 1006 g/d, 75 g/d, 19.2 MJ/d, 74.0% of gross energy, and 66.2% of grossenergy, respectively. The feed efficiency ratio (FCR), gross energy efficiency, digestible energyefficiency, and metabolizable energy efficiency were 7.38%, 3.86 g ADG/MJ, 5.24 g ADG/MJ, and 5.84g ADG/MJ, respectively. It is concluded that time of feeding did not affect the dietary energy utilizationin local rams.